Politeness Strategies Used by Emily Cooper to Her Boss and Work Colleagues in Emily in Paris - Tiffany Liman (Kata Kita: Journal of Language, Literature, and Teaching, 2024)
This qualitative research study was conducted to analyze the politeness strategies used by Emily Cooper to her boss and work colleagues throughout season 3 of the Netflix series Emily in Paris, specifically within the business context. The main theory used is Watts’ second order politeness strategy (2003) that is elaborated with the politeness strategy theory by Brown and Levinson (1987). The findings indicate that Emily Cooper used more politeness sub strategies to her boss who has a higher social status than hers rather than to her work colleagues who have the same social status as hers. Additionally, the findings revealed that one out of the four politeness strategies Emily Cooper does not use to her boss, whereas she used it to her work colleagues, is the off record politeness strategy. In conclusion, in this study the politeness strategies used by Emily Cooper to both her boss and work colleagues in the series Emily in Paris season 3 depended on the social status of the person she talked to during communicating about work.